Typologies and Correlates of Police Violence Against Female Sex Workers Who Inject Drugs at the México–United States Border: Limits of De Jure Decriminalization in Advancing Health and Human Rights - West, Brooke S. (Journal of interpersonal violence, 2022)
Decriminalization of sex work is increasingly promoted as a structural measure to improve the health of vulnerable groups. In México, sex work is not illegal, but knowledge of policies? street-level impact is limited. This study describes typologies of police violence against female sex workers who inject drugs (FSWID), identifying risk and protective factors for violence exposure to inform policy responses. Survey data were collected during 2008?2010 among HIV-negative FSWID in a behavioral intervention in Tijuana and Ciudad Juarez (N = 584). Latent class analysis identified typologies of police violence in the past 6 months: asked for money, money taken, syringes taken, asked for sex, and sexually assaulted. Structural equation modeling (SEM) predicted latent class membership using sociodemographic, behavioral and risk environment factors, controlling for age, education, marital status, and city. Recent police violence was reported by 68% of FSWID, with three typologies emerging: Low (36.6%); Material (47.8%): having money/syringes taken or being asked for money; and Material/Sexual (15.7%): material violence and being asked for sex or sexually assaulted. In multivariable SEM, Material Violence was associated with: being jailed [adjusted Odds Ratio (aOR) = 4.34], HIV testing (aOR = 2.18), and trading sex indoors (aOR = 1.66). Factors associated with Material/Sexual Violence included: being jailed (aOR = 41.18), injecting with clients (aOR = 3.12), earning more money for sex without a condom (aOR = 2.88), being raped by a client (aOR = 2.13), drinking with clients (aOR = 2.03), receiving substance use treatment (aOR = 1.95), being <18 when first trading sex (aOR = .43), trading sex outdoors (aOR = .53), and poor working conditions (aOR = .56). Despite de jure decriminalization of sex work, police violence against FSWID at the México?United States border is pervasive with implications for sex- and drug-related harms. Closing gaps in policy implementation and mitigating material/sexual violence from police is imperative to decreasing economic vulnerability, risk of overdose and HIV, and improving engagement in HIV and harm reduction services.